Efektivitas Penggunaan Media Patchboard terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas V SD 2 Getassrabi - Zakiyati, Nor Meilin; Kironoratri, Lintang; Rondli, Wawan Shokib (AS-SABIQUN, 2024)
The aim of this research is to measure the effectiveness of using Patchboard as a learning medium in Pancasila Education subjects in class V of SD 2 Getassrabi. This quantitative research was carried out using experimental methods. This research was designed using a quantitative One-group Pretest Posttest design. This research was conducted during the even semester of the 2023/2024 academic year. All fifth grade students at SD 2 Getassrabi Gebog Kudus, consisting of 12 students, were included in the sample of this research. This research uses the Paired Sample T-Test to find out how significant the effect of increasing pretest and posttest learning outcomes is. The results of the Paired Sample T-Test analysis show that the significance level with sig. (2-tailed) of 0.000 (p0.05) or 0.000 less than 0.05, which shows that the use of Patchboard media has an effect on the learning outcomes of class V students at SD 2 Getassrabi on the material of the unity and unity of the Republic of Indonesia. Apart from that, to find out the percentage influence of using Patchboard media, an N-Gain test was carried out. The results of the N-gain percent test showed an increase in the pretest posttest of 46%, meaning that the effectiveness of using Patchboard media on the learning outcomes of class V students at SD 2 Getassrabi was 46% at a less effective level.